Glow discharge with a hollow cathode in carbon dioxide - Lisovskiy, V.A.; Dudin, S.V.; Platonov, P.P.; Osmayev, R.O.; Yegorenkov, V.D. (Problems of Atomic Science and Technology, 2022)
This paper is devoted to an experimental study of the dc discharge with a hollow cathode within the carbon dioxide pressure range of 0.06…2 Torr. The registered CVCs in the pressure range below 0.5 Torr possess a hysteretic pattern with transitions between glow and hollow modes. We have demonstrated that the value of the product of gas pressure and distance between cathode plates p·dh = 0.32 Torr·cm is optimum for the application of the discharge with hollow cathode for plasma conversion of the carbon dioxide when the maximum discharge current is observed. Then the cathode cavity is filled with a high density discharge. Treating the optical emission spectrum has revealed that in the negative glow there have to be present the electron flows with the energy above 18 eV, what must provide the high rate of the CO₂ molecules conversion via direct electron impact. Slow electrons produced inside the negative glow itself have to supply an additional contribution to the conversion process and to make an efficient excitation of oscillatory levels of CO₂ molecules. Представлено експериментальне дослідження жеврійного (тліючого) розряду з порожнистим катодом у діапазоні тиску вуглекислого газу 0,06…2 Toрр. Виміряні вольт-амперні характеристики в діапазоні тиску менше 0,5 Торр мають гістерезисний характер з переходами від тліючого до порожнистого режимів. Показано, що оптимальними для використання розряду з порожнистим катодом для плазмової конверсії вуглекислого газу є величина добутку тиску газу і відстані між катодними пластинами p·dh = 0,32 Toрр·cм, коли спостерігається максимальний розрядний струм. При цьому катодна порожнина заповнена розрядом із високою густиною. Аналіз виміряного оптичного емісійного спектра показав, що в негативному світінні в катодній порожнині мають бути потоки електронів з енергією вище 18 еВ, що повинно забезпечувати високу швидкість процесу конверсії молекул CO₂ прямим електронним ударом. Додатковий внесок у процес конверсії мають давати повільні електрони, народжені в негативному світінні, які ефективно збуджують коливальні рівні молекул CO₂.